Transcatheter mitral valve repair: where are we?. (December 2014) - Merk, Denis Rouven; Emrich, Fabian C; Mohr, Friedrich Wilhelm; Seeburger, Joerg
<x xml:space="preserve">Abstract</x> Mitral valve regurgitation is the second most common form of valve pathology after aortic stenosis needing surgery. While open surgical repair is still the gold standard, innovative interventional approaches have emerged as an alternative treatment option for high-risk patients. While only a few of these new techniques have been approved for the clinical setting, many others are currently under development or in pre-clinical testing. This editorial will attempt to summarize all current transcatheter-based innovations targeting the mitral valve and explore their potential for the future.